Development of liquid spray triggering and control - Raja Sharul Azuan, Raja Kamaralzaman (2010)
This project presents the study about development of liquid spray triggering and control in a direct injection gasoline injector of a gasoline engine. The objectives of the study is to develop control system using a parameters of time and pressure in order to identify the spray characteristics including spray angle, spray tip penetration and spray width. The scopes of this research are choosing control system due to type of injection, setup test rig for experimental using high pressure chamber and develop control and triggering system in order to control the timing and delay of the injector. After test rig fabrication is done and all equipment has been setup, experiment is done by supplying pressure at 4 Bar from high pressure pump to fuel injector that attach to high pressure chamber. Ambient temperature was set to 300 K and ambient pressure is 0.1 Mpa. Simple triggering and control has been developing using MATLAB Simulink and the result was analyzed due to sample of calculation.